Overlapping rheumatoid meningitis with anti‐N‐methyl‐D‐aspartate receptor encephalitis: A case report. Issue 4 (22nd April 2023) - Ide, Toshihiro; Kawanami, Takeru; Tada, Yoshifumi; Eriguchi, Makoto
Abstract: A 66‐year‐old woman in treatment for rheumatoid meningitis was found to be positive for anti‐N‐methyl‐D‐aspartate receptor (NMDAR) antibodies in the cerebrospinal fluid, and intravenous immunoglobulin improved her psychiatric symptoms. The co‐existence of NMDAR antibodies should be considered in cases of poor response to treatments or atypical symptoms in rheumatoid meningitis.